Dampak Penggunaan Aplikasi Wordwall terhadap Hasil Belajar Siswa dalam Pembelajaran IPAS di Kelas V Sekolah Dasar - Siti Sarah Aulia; Atep Lesmana; Syarif Hendriana (STKIP Subang, 2026)
Students' low learning interest in Natural and Social Sciences (IPAS) remains a challenge in elementary education, primarily due to the limited use of interactive learning media. This study aimed to examine the effect of the Wordwall application on the learning interest of fifth-grade students at SDN 2 Nagri Tengah. A quantitative approach with a survey method was employed involving 28 students as the research sample. Data were collected using questionnaires and analyzed through descriptive statistics, classical assumption tests, simple linear regression, hypothesis testing, correlation analysis, and the coefficient of determination. The findings revealed that the use of Wordwall had a positive and significant effect on students' learning interest, as indicated by the regression equation Y = 58.783 + 0.367X. The partial test produced a t-value of 3.441 with a significance level of 0.002, while the simultaneous test yielded an F-value of 11.840 with a significance level of 0.002. The coefficient of determination (R² = 0.313) indicates that Wordwall contributed 31.3% to students' learning interest. Therefore, Wordwall can be considered an effective interactive learning medium for enhancing students' learning interest in IPAS.